Analisis Jaringan Komunikasi Duta Universitas Trunojoyo Madura dalam Membangun Solidaritas Internal: Indonesia - Kirana Putri Adinda; Safira Dwi Agustina; Rio Kurniawan (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
The internal communication network of student organizations plays a strategic role in supporting the success of programs while strengthening solidarity among members. This study examines the communication network patterns within the Gelora Ramadhan program committee of the Campus Ambassador of Universitas Trunojoyo Madura (UTM) and their contribution to organizational internal solidarity. A quantitative descriptive method with a Social Network Analysis (SNA) approach was employed, involving 24 committee members as the unit of analysis. Data were collected through interviews and dichotomous-scale sociometric questionnaires, subsequently processed using UCINET VI software and visualized through NetDraw. The findings reveal that the committee's communication network forms a centralized pattern, with the Person-in-Charge and the Executive Chair serving as dominant actors (degree centrality = 1.000; betweenness = 29.447). Division coordinators function as secondary brokers bridging communication between the Executive Board and operational members. An open and egalitarian communication pattern, supported by a collective deliberation system and multi-platform digital media, effectively reinforces both intra-division and inter-division solidarity simultaneously. These findings affirm that the effectiveness of internal communication depends not solely on hierarchical structure, but on the quality of relationships and the openness of information channels within the organization.